2010
DOI: 10.1186/1471-2105-11-109
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer classification based on dimensionality reduction for SELDI-TOF data

Abstract: BackgroundRecent advances in proteomics technologies such as SELDI-TOF mass spectrometry has shown promise in the detection of early stage cancers. However, dimensionality reduction and classification are considerable challenges in statistical machine learning. We therefore propose a novel approach for dimensionality reduction and tested it using published high-resolution SELDI-TOF data for ovarian cancer.ResultsWe propose a method based on statistical moments to reduce feature dimensions. After refining and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…In [8], it is claimed that statistical moments preserve the data properties while reducing the dimensionality. Although they achieved a reasonable classification performance, it is shown that statistical moments lose some of the useful discriminatory information when compared to the wavelet analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In [8], it is claimed that statistical moments preserve the data properties while reducing the dimensionality. Although they achieved a reasonable classification performance, it is shown that statistical moments lose some of the useful discriminatory information when compared to the wavelet analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In [8], the same statistical moments are used to classify ovarian cancer MS data. In the classification phase of this study, KPLS (Kernel Partial Least Square) method is used.…”
Section: Dimension Reduction Stagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Surfaceenhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF-MS) combined with ProteinChip technology is a high-throughput proteomic analysis approach which has been shown to be effective in the detection of biomarkers for early stage malignancy (Petricoin and Liotta, 2004). Using this combined technology, some new serum biomarkers with higher sensitivity were found for the early detection of different cancers, including prostate cancer (Okamoto et al, 2009;Yamamoto-Ishikawa et al, 2009), ovarian cancer (Høgdall et al, 2010;Tang et al, 2010), brain cancer , colorectal cancer (Yu et al, 2004;Helgason et al, 2010), breast cancer (Hu et al, 2005;Opstal-van Winden et al, 2011), lung cancer (Rathinam et al, 2011), and pancreatic cancer (Felix et al, 2011). However, reports on the protein profiling of different stages of ESCC development have not yet been published.…”
Section: Introductionmentioning
confidence: 99%